The Implication of Teachers' Question and Feedback to the Students Vocabulary Production: an Analysis of Spoken Discourse of EFL Classrooms using IRF Model - Purnawati, Purnawati (Foremost Journal, 2021)
This research was conducted to investigate teacher-students interaction in two different English classrooms. A descriptive analysis method was employed by analyzing the interaction using the Initiation, Response, and Feedback (IRF) model. Within the interaction, the teachers' questions, feedback, and students' vocabulary production are the main focus in this research. The result showed that the two classrooms have different IRF interaction patterns as well as the teachers' choice of questions and feedback types. In response to the teachers' talk, the students provide different frequencies and a variety of vocabulary.  In short, classroom B with a more open-ended question and active feedback prompt more students' vocabulary production. The implication of this research is that this research highlights that teachers' strategies of questioning and giving feedback in the class strongly impact the students' vocabulary production.